2020
DOI: 10.1016/j.enbuild.2019.109635
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis of Life Cycle Energy Assessment in Early Stages of Design

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…Our analysis provides guidance toward which parameter's uncertainty to reduce first to get a more precise indication of environmental impact. A previous study [21] showed that this method can also applied to the entire life cycle including operational energy consumption. Future work should add other criteria (such as cost) and take into account the multi-criterial nature of decision processes in building design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis provides guidance toward which parameter's uncertainty to reduce first to get a more precise indication of environmental impact. A previous study [21] showed that this method can also applied to the entire life cycle including operational energy consumption. Future work should add other criteria (such as cost) and take into account the multi-criterial nature of decision processes in building design.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reinforcement amount is needed for concrete building parts only and is defined to be the mass (kg) of reinforcing steel per volume (m 3 ) of concrete. As we are analyzing embedded impacts in more detail, the number of parameters is reduced compared to our previous study concerned with LCEA [21]. Also, the reduced number of parameters allows us to regroup them differently providing a more specific analysis.…”
Section: Sampling Process Sensitivity and Contribution Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…• studies focusing on the entire building. In these studies, comprehensive LCA databases are used, and the studies focus on the performance of the entire building, mainly through matrices in which the building of quantities is combined with the environmental indicators of individual building materials [90,91] LCA application in the building sector could be employed either for building components and materials, or for the entire building ( Figure 12). Numerous LCA databases (academic, commercial, or public) which are used in the building sector.…”
Section: Environmental Assessment Of Building Products and Buildings:mentioning
confidence: 99%
“…• studies focusing on the entire building. In these studies, comprehensive LCA databases are used, and the studies focus on the performance of the entire building, mainly through matrices in which the building of quantities is combined with the environmental indicators of individual building materials [90,91] • the integration of LCA databases into BIM models for the assessment of the entire building at the design stage [68,69,92,93]. This trend is anticipated to prevail in the near future, whereas commercialized tools, such as Tally, have already been launched [94].…”
Section: Environmental Assessment Of Building Products and Buildings:mentioning
confidence: 99%